Tension-Type, the Forgotten Headache A Common but under Treated Condition - Kundu, Narayan Chandra; Ahmad, Quamruddin (TAJ: Journal of Teachers Association, 2009)
Headache is a universal problem. Of all the types of headache, the commonest is Tension-type Headache. The word 'tension' implies that this type of headache can be attributed entirely to tension or stress, which may make people with this type of headache reluctant to consult a physician. Physicians misperceptions that tension-type headache are mild, benign, self-treatable and occur solely due to stress may further trivialize the problem. Thus this disease is often under-diagnosed and not treated properly. This article describes the disease and its management and is being published to increases awareness of the disease amongst the physicians. doi: 10.3329/taj.v17i2.3462 TAJ 2004; 17(2): 121-128